If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8 = y + 3 Reorder the terms: -8 = 3 + y Solving -8 = 3 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. -8 + -1y = 3 + y + -1y Combine like terms: y + -1y = 0 -8 + -1y = 3 + 0 -8 + -1y = 3 Add '8' to each side of the equation. -8 + 8 + -1y = 3 + 8 Combine like terms: -8 + 8 = 0 0 + -1y = 3 + 8 -1y = 3 + 8 Combine like terms: 3 + 8 = 11 -1y = 11 Divide each side by '-1'. y = -11 Simplifying y = -11
| =(4t-4)-(2t^2+5) | | 5x^2-16=36 | | 40+x=2014 | | 0.59N=100gu | | u-1/3=-4/5 | | (45+50b)= | | 3v=7.5 | | 0.59N= | | 25=x+2x+(1+5x) | | =25x+2x+(1+5x) | | (x-10)+(x+30)=120 | | 12n^2-8n=0 | | 100gu= | | -5/6/x=-1/22/3 | | 7x-6x+x-5+3x= | | 11/x-4 | | 7-3[2-(5y-3)]= | | 2a^2-a-1=0 | | 30-2(-6)= | | (y-7)(2y+5)=0 | | 18+4(p-9)=36 | | 1.5x+6=-1.5x+12 | | 4+256x^3=0 | | 2v^2-5=-3v | | 49x^2-56x-159=0 | | s=0.164t-0.65 | | 3/7a=-5 | | 2v^2-5=0 | | 971-((4+788))x(470-454)= | | -d/4=-4.7 | | 2(9x+9)= | | 6r+7+5r+2r=19 |